If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -6p + 5p + -4 = 0 Reorder the terms: 10 + -4 + -6p + 5p = 0 Combine like terms: 10 + -4 = 6 6 + -6p + 5p = 0 Combine like terms: -6p + 5p = -1p 6 + -1p = 0 Solving 6 + -1p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1p = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1p = 0 + -6 -1p = 0 + -6 Combine like terms: 0 + -6 = -6 -1p = -6 Divide each side by '-1'. p = 6 Simplifying p = 6
| 5+2(n+1)=2h | | -4(2t-t)+5t=4t-2 | | 3(5x-7)-12x=-9 | | 6x-10=-8+8x | | x(a-b)=d+c | | 200=n+6(8+3n) | | -3/8x-4=1/8x-5 | | D=Ty | | 6*5+3=y | | 5g-2h=-5 | | 3x+9=7x-5 | | 122=9/5c+32 | | 4w+12(w-1)=36 | | 2(x+5)+3(x-5)=180 | | -5b=-8 | | 4x^2+8x=320 | | 21d-4=-67 | | -5(2t-3)+2t=8t-6 | | 8-2x+8+1=5x+5+1 | | 3*x-4=11 | | 3(4y-21)=7 | | 0.25x+7=0.33x-8 | | loge(x^2)-2=0 | | -2xy=-3 | | 15-.75z=13-.50z | | -6+3v+v=6 | | r+26-32r=-41 | | 8x^2-16x-8=0 | | -3(4t-5)+2t=6t-4 | | 2x+[5x(-2x-3x)]= | | 6x-10=2x-2 | | X=4x+8x |